2013
DOI: 10.1007/s00395-013-0370-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of electromechanical coupling between KV and CaV1.2 channels to coronary dysfunction in obesity

Abstract: Previous investigations indicate that diminished functional expression of voltage-dependent K+ (KV) channels impairs control of coronary blood flow in obesity/metabolic syndrome. The goal of this investigation was to test the hypothesis that KV channels are electromechanically coupled to CaV1.2 channels and that coronary microvascular dysfunction in obesity is related to subsequent increases in CaV1.2 channel activity. Initial studies revealed that inhibition of KV channels with 4-aminopyridine (4AP, 0.3 mM) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…4) We investigated the role of KV7 channels in coronary metabolic vasodilation (using a subset of animals; n ϭ 2) by pacing the heart to higher rates before and during intracoronary infusion of 10 M linopirdine. In this experiment, arterial and coronary venous blood were sampled simultaneously at each heart rate to calculate myocardial oxygen consumption by the Fick principle (5). We assessed the role of K V7 channels in endothelium-dependent vasodilation by performing intracoronary bradykinin concentration-response protocols before (control) and during simultaneous infusion of 30 M linopirdine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) We investigated the role of KV7 channels in coronary metabolic vasodilation (using a subset of animals; n ϭ 2) by pacing the heart to higher rates before and during intracoronary infusion of 10 M linopirdine. In this experiment, arterial and coronary venous blood were sampled simultaneously at each heart rate to calculate myocardial oxygen consumption by the Fick principle (5). We assessed the role of K V7 channels in endothelium-dependent vasodilation by performing intracoronary bradykinin concentration-response protocols before (control) and during simultaneous infusion of 30 M linopirdine.…”
Section: Methodsmentioning
confidence: 99%
“…The specific redox-sensitive targets mediating H 2 O 2 -induced vasodilation of coronary vascular smooth have not been firmly established. Our previous findings suggest that voltage-dependent K ϩ (K V ) channels may play an important role, but the identities of individual K V channels involved remain elusive (4,5,12,38,39). K V 7 channels are expressed in a variety of vascular smooth muscle cell types, including those from the coronary circulation (20,23).…”
mentioning
confidence: 99%
“…Witczak et al and others 37 also demonstrated decreases in VGCC function with disease. However, Neeb et al 22 demonstrated a decrease in SERCA function with disease, and several studies 20, 38, 39 reported an increase in VGCC function with disease. One possible explanation for the apparent discrepancy in the data is duration of diet and/or severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…An additional factor in these discrepancies may be the swine model. Witczak 19 and Hill 21 utilized diabetic dyslipidemic Yucatan swine that had no primary insulin resistance, while Berwick 20 utilized MetS Ossabaw swine with primary insulin resistance, hypertension, and increased aldosterone as major characteristics. Neeb 22 used both Ossabaw and Yucatan swine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation